Respon Pertumbuhan Bibit Kelapa Genjah Terhadap Berbagai Dosis Pupuk Organik [The Response of Dwarf Coconut Seedling Growth on the Different Dose of Organic Fertilizer] - Alfred Pahala Manambangtua, SP; Linda Trivana; Yulianus Rompah Matana (Pusat Penelitian dan Pengembangan Perkebunan, 2018)
One of the way to reduce the negative impact of the use of inorganic fertilizer is the using of organic fertilizer. Organic fertilizer in compsted form of compos has an important role in the improvement of chemical, physical, and biological of the soil and as a source plants nutriens. The organic fertilizer used in this research comes from coconut coir dust and composting of goat manure. Dust husk contains nutrient elements such as N, P, K, Ca, Fe, Mg, Na, Mn, Cu, Zn and Al. Goat manure contains relatively high nutrients because the goat muck is mixed with urine which also contains nutrients. Coir dust is a waste of coconut fiber. This research aims to determine the response of seedling growth of coconut seedling to organic fertilization. The research was conducted at Greenhouse, Indonesian Palma Plant Research Institute, from September to March 2017. The research used Completely Randomized Design (RAL) with five treatments and six replications to obtain 30 experimental units. The treatment tested was the dosage of organic fertilizer seedlings, consisting of no organic fertilizer (control), 250 g organic fertilizer, 500 g organic fertilizer, organic fertilizer 750 g, organic fertilizer 1.000 g. Organic fertilizer gives a real effect on plant height, stem circumference, and the content of K elements in the plant tissue. However, organic fertilizer fertilization does not affect for the number of leaves, root dry weight, dry weight of stem, the content of N and P elements in plants significantly. The use of organic fertilizer on coconut seeds can reduce the cost of fertilization using inorganic fertilizers and improve soil structure.ABSTRAKSalah satu cara untuk mengurangi dampak negatif dari penggunaan pupuk anorganik adalah penggunaan pupuk organik. Pupuk organik dalam bentuk yang telah dikomposkan berperan penting dalam perbaikan sifat kimia, fisika, dan biologi tanah serta sebagai sumber nutrisi tanaman. Pupuk organik yang digunakan dalam penelitian ini berasal dari debu sabut kelapa dan pengomposan kotoran kambing. Debu sabut mengandung unsur hara seperti N, P, K, Ca, Mg, Fe, Na, Mn, Cu, Zn, dan Al. Kotoran kambing mengandung unsur hara yang relatif tinggi karena kotoran kambing tercampur urine yang juga mengandung nutrisi. Debu sabut merupakan limbah dari penyeratan sabut kelapa. Penelitian ini bertujuan untuk mengetahui respon pertumbuhan bibit kelapa genjah terhadap pemupukan organik. Penelitian dilaksanakan di Rumah Kaca, Balai Penelitian Tanaman Palma, Manado dari bulan September-Maret 2017. Penelitian menggunakan Rancangan Acak Lengkap (RAL) dengan lima perlakuan dan enam ulangan sehingga diperoleh 30 satuan percobaan. Perlakuan yang diuji adalah dosis pupuk organik perbibit, yang terdiri atas tanpa pemberian pupuk organik (kontrol), pupuk organik 250 g, pupuk organik 500 g, pupuk organik 750 g, pupuk organik 1.000 g. Pemberian pupuk organik memberi pengaruh nyata terhadap tinggi tanaman, lingkar batang, dan kandungan unsur K dalam jaringan tanaman. Namun pemupukan pupuk organik tidak mempengaruhi untuk jumlah daun, berat kering akar, berat kering batang, kandungan unsur N dan P pada tanaman secara nyata. Penggunaan pupuk organik pada bibit kelapa dapat mengurangi biaya pemupukan menggunakan pupuk anorganik dan memperbaiki struktur tanah.